OS 13-06 GENERATION OF AORTIC FLOW VELOCITY FROM DERIVED AORTIC PRESSURE WAVEFORMS USING AGE-SPECIFIC AORTIC IMPEDANCE MODELLING. (September 2016) - Adji, Audrey; Weber, Thomas; O'Brien, Caroline; O'Rourke, Michael; Avolio, Alberto
Abstract : Objective: Relative ease of estimating of Ascending Aortic (AA) pressure non-invasively enables interpretation of age-related pressure waveform changes due to altered pulse wave propagation. AA flow velocity waveforms, measured invasively by ElectroMagnetic (EM) cuff/ catheter, and non-invasively by Cardiac Magnetic Resonance (CMR) also show characteristic aging changes attributable to aortic dilation and subtle impairment of Left Ventricular (LV) function. Conventional Doppler waveforms do not. Design and Method: AA flow velocity waveforms were generated in 161 male subjects (21–80 years) undergoing cardiac catheterisation for suspected coronary disease, in whom AA pressure was derived from radial pressure waveforms using SphygmoCor. This pilot study is based on known age-related changes in AA impedance (from previously acquired carotid pressure and CMR flow velocity data) using mathematical relations governing flow and pressure in frequency domain, and solved using discrete Fourier transform analysis (Matlab v2014). The generated AA flow velocity waveforms were then compared to Doppler flow tracings. SphygmoCor studies and echocardiography were performed within 1 hour. Results: As with CMR and EM, pressure-derived AA flow velocity wave amplitude and contour showed considerable change with age. This, however, was not always apparent in Doppler-measured flow waves. Estimated AA flow waves showed a PFV which corresponded well to the initial pressure peak (100–140 msec after the wavefoot). PFV measured by Doppler (mean 105+18 cm/s) was constant across the age range, while PFV estimated by our model decreases as age increases (39+10 cm/s) (figure) (p < 0.001). Conclusions: Model-estimated AA flow waves showed definite aging changes and are consistent with EM and CMR values. Generation of AA flow velocity from AA pressure and AA impedance can be achieved, and appears to confirm that AA impedance measured non-invasively is a satisfactory measure of hydraulic load to the heart. Anomalies between the three flow methods described here and Doppler need be confirmed and explained.